Optimal monetary policy responses and welfare analysis within the highfrequency New-Keynesian framework - Stephen Sacht (Kiel University, Department of Economics, 2014)
In this we investigate the welfare effects of optimal monetary policy measurements within a high-frequency New-Keynesian model i.e. under variation of the period length. Our results indicate that the policy maker faces a higher welfare loss on a higher relative to a lower frequency of the agents' decision making. While overall inertia in the model increases, we show that the more the pass-through of output gap movements into inflation rate dynamics is dampened on a higher frequency, this amplifies the trade-off of the central bank in case of a cost-push shock. This is caused by the impact of so-called frequency-dependent persistence effects, which mimic the impact of the increase in the amount of market days on the dynamics of the model. This result is less severe in the optimal monetary policy regime under Commitment because of a time-invariant history dependence effect with respect to the period length.
Keywords: C61; C63; E32; E52; 330; Hybrid New-Keynesian model; high-frequency modelling; optimal monetary policy; frequency-dependent persistence